Analysis of diastasis recti abdominis phenotypes and related delivery factors at 42 days postpartum - Jingjing Guo; Lingyan Liu; Min Hua; Dong Han; Xuezhen Tang; Jiying Wen; Yuheng Zhou (Annals of Medicine)
Objective Diastasis recti abdominis (DRA) is highly prevalent in the postpartum period and affects women’s health. However, the relationship between DRA and prenatal and intrapartum factors is unclear. This study aimed to investigate DRA phenotypes and assess the influence of prenatal and intrapartum factors at 42 days postpartum.Materials and methods This retrospective study included 1438 singleton primiparous women who delivered between January 2023 and January 2024 at a single institution. The median age was 29 years, and the median gestational age at delivery was 274 days. The exclusion criteria included factors that might affect intra-abdominal pressure during the pre-pregnancy and pregnancy periods. DRA was defined as an inter-rectus distance of ≥20 mm at any of the three measurement sites: 3 cm above/below the umbilicus and at the umbilicus, measured by ultrasound. The Kruskal-Wallis and chi-square tests were used for variance analysis and comparison of variables, respectively. Multivariate logistic regression analysis was performed to explore the relationships between DRA phenotypes and these factors.Results The incidence of DRA was 89.4%, 47.8% of which presented as combined upper umbilical and periumbilical separation, 33.7% as isolated periumbilical separation, 6.7% as complete separation, and 10.6% without separation. The combined separation of the upper umbilical and periumbilical areas was associated with increased BMI, neonatal weight, vaginal delivery, episiotomy, and perineal laceration. Complete separation was associated with BMI, neonatal weight, and vaginal delivery. Isolated periumbilical separation was associated with neonatal weight, vaginal delivery, episiotomy, perineal laceration, and cesarean during the first stage of labor. Vaginal delivery was negatively correlated with DRA.Conclusion DRA is highly prevalent at 42 days postpartum, with different phenotypes having distinct prenatal and intrapartum risk factors. Careful weight management during pregnancy, promotion of vaginal delivery, and rational use of perineal episiotomies may reduce the incidence of DRA in primiparous women.